Livestock production on Masai group ranches. 1. A preliminary survey of the goat and sheep populations at Elangata Wuas - Wilson, R.T. (1978)
Presents results of a preliminary survey of goat & sheep populations at the Elangata Wuas group ranch, providing information on breed type, physical characteristics, population structure by sex & age, & average growth rates os sheep & goats on the ranch.